Peripheral NK cell phenotypic alteration and dysfunctional state post hepatitis B subviral particles stimulation in CHB patients: evading immune surveillance - Selim, Mohamed A; Suef, Reda A.; Saied, Ebrahim; Abdel-Maksoud, Mostafa A.; Almutairi, Saeedah Musaed; Aufy, Mohammed; Mousa, Adel A.; Mansour, Mohamed T. M.; Farag, Mohamed M. S. (Frontiers in Immunology, 2024)
Background The relationship between chronic hepatitis B (CHB) infection and natural killer (NK) cell dysfunction is well-established, but the specific role of HBV viral antigens in driving NK cell impairment in patients with CHB remains unclear. This study investigates the modulatory effects of hepatitis B virus subviral particles (HBVsvp, a representative model for HBsAg) on the phenotypic regulation (activating and inhibitory receptors), cytokine production and cytotoxic potential of peripheral blood mononuclear cell-derived natural killer cells (PBMCs-derived NK cell), which contributes to NK cell dysfunction in CHB infection, potentially serving as an effective HBV immune evasion strategy by the virus. Methods NK cells were isolated from peripheral blood of patients with CHB (n=5) and healthy individuals (n=5), stimulated with HBVsvp. Subsequent flow cytometric characterization involved assessing changes in activating (NKp46 and NKG2D) and inhibitory (CD94) receptors expression, quantifying TNF-α and IFN- γ cytokine secretion, and evaluating the cytotoxic response against HepG2.2.15 cells with subsequent HBVsvp quantification. Results In CHB patients, in vitro exposure of PBMCs-derived NK cell with HBVsvp (represent HBsAg model) significantly reduced NK cell-activating receptors expression (P = 0.022), increased expression of CD94 + NK cells (p = 0.029), accompanied with a reduced TNF-α - IFN-γ cytokine levels, and impaired cytotoxic capacity (evidenced by increased cell proliferation and elevated HBVsvp levels in co-cultures with HepG2.2.15 cells in a time-dependent), relative to healthy donors. Conclusion These findings suggest that HBVsvp may induce dysfunctional NK cell responses characterized by phenotypic imbalance with subsequent reduction in cytokine and cytotoxic levels, indicating HBVsvp immunosuppressive effect that compromises antiviral defense in CHB patients. These data enhance our understanding of NK cell interactions with HBsAg and highlight the potential for targeting CD94 inhibitory receptors to restore NK cell function as an immunotherapeutic approach. Further clinical research is needed to validate these observations and establish their utility as reliable biomarkers.